2015
DOI: 10.6002/ect.2014.0023
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Hematopoietic stem cell transplantation is a life-saving treatment, but donor numbers are lacking in Turkey and elsewhere. Increased awareness of hematopoietic stem cell transplantation among university students might help expand donation. We evaluated the effect of a brief targeted educational intervention on knowledge and attitudes about hematopoietic stem cell transplantation and donation among first-year university students in Turkey. Materials and Methods: There were 301 first-year university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…In the post-tests, however, the knowledge of the experimental group was significantly higher than that of the control group. This is the same as the findings by Kaya et al [14], which reported that the knowledge and awareness of HSCT improved after the first-year HSCT students in medical school. Based on the findings of Kim and Ahn [15] and Kwok et al [18] that higher knowledge level leads to higher level of willingness for HSCD, it is expected that the promotion of knowledge about the benefit of HSC, diseases requiring HSCT, the HSCD registration procedure, and the procedure and methodologies of HSCT can also improve the willingness for HSCD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the post-tests, however, the knowledge of the experimental group was significantly higher than that of the control group. This is the same as the findings by Kaya et al [14], which reported that the knowledge and awareness of HSCT improved after the first-year HSCT students in medical school. Based on the findings of Kim and Ahn [15] and Kwok et al [18] that higher knowledge level leads to higher level of willingness for HSCD, it is expected that the promotion of knowledge about the benefit of HSC, diseases requiring HSCT, the HSCD registration procedure, and the procedure and methodologies of HSCT can also improve the willingness for HSCD.…”
Section: Discussionsupporting
confidence: 91%
“…This shows that the educational program for HSCD promotion was effective in improving the attitude toward HSCD. The HSCT education provided for medical students in the study by Kaya et al [14] led to more positive attitudes toward HSCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the lack of response, the items themselves are hugely important; shorter questions and surveys, engagement to the subject, personalization of the questionnaire, and yes/no questions will attribute to a higher response rate. 6 9 Survey mode, number and type of follow up, type of interviewee, and geographic variance also significantly impact response rate. 10 – 13 These measurable aspects of response rate comprise a considerable, but only a part, of the puzzle.…”
mentioning
confidence: 99%
“…Providing accurate information and knowledge about stem cell donation remains a priority in increasing the number of donations. Recent studies have demonstrated that also educational and communicative efforts towards the medical community may be beneficial in the recruitment and retention of donor populations [61, 62]. The creation of a social and cultural atmosphere favouring the diffusion of correct and proper information regarding HSC donation is central in encouraging people to make a donation.…”
Section: Bioethical Issuesmentioning
confidence: 99%